2010
DOI: 10.4103/1817-1737.58955
|View full text |Cite
|
Sign up to set email alerts
|

Home-based pulmonary rehabilitation program: Effect on exercise tolerance and quality of life in chronic obstructive pulmonary disease patients

Abstract: BACKGROUND:A key component in the management of chronic obstructive pulmonary disease (COPD) patients is pulmonary rehabilitation (PR), the corner stone of which is exercise training.AIM:This study aims to evaluate the effect of a two-months, home-based PR program with outpatient supervision every two weeks, on exercise tolerance and health-related quality of life (HRQL) using Arabic-translated standardized generic and specific questionnaires in COPD patients recently recovered from acute exacerbation,DESIGN:R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 35 publications
(62 reference statements)
2
94
1
Order By: Relevance
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Finally, there was a significant decrease in sensation of dyspnea assessed by MRC in HCPR compared to controls (-0.21, 95%CI: -0.42 to -0.00, I 2 = 0%) ( Figure 6). (b) Quality of Life: Thirteen studies 17,18,19,31,33,34,36,38,42,44,46,47,49 (n = 521) assessed quality of life with CRQ and four 18,30,39,48 (n = 281) with SGRQ. The meta-analysis showed that participants who received the intervention showed significant improvement in the four quality of life domains as- Figure 3 Graph on risk of bias for each selected study.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations